Melanoma Ex Blue Nevus With GNA11 Mutation and BAP1 Loss: Case Report and Review of the Literature. (November 2020) - Chang, Li-Wei; Kazlouskaya, Viktoryia; Kazi, Rashek; Davar, Diwakar; Ferris, Robert L.; Ho, Jonhan; Karunamurthy, Arivarasan; Jedrych, Jaroslaw J.; Bunimovich, Yuri L.
Abstract : Abstract: Cutaneous melanomas may demonstrate a variety of histopathological features and genetic abnormalities. Melanomas that arise in the setting of blue nevi, also known as "malignant blue nevus" or melanoma ex blue nevus (MBN), share a similar histopathological and mutational profile with uveal melanoma. Most uveal melanomas show characteristic GNA11 or GNAQ mutations; additional BAP1 mutation or loss is associated with the highest risk of metastasis and worst prognosis. However, the significance of BAP1 loss in melanomas ex blue nevus remains unclear. We present a case of MBN arising from the scalp of a 21-year-old woman. The diagnosis was established on histopathological findings demonstrating a markedly atypical melanocytic proliferation with increased mitotic activity, necrosis, and a focus of angiolymphatic invasion. Immunohistochemical analysis demonstrated the absence of BAP1 nuclear expression within tumor cells. Next generation sequencing detected GNA11 Q209L mutation and BAP1 loss (chromosome 3p region loss), supporting the diagnosis. We reviewed another 21 MBN cases with reported BAP1 status from the literature. MBN with BAP1 loss presented at a younger average age (41 vs. 61 years), demonstrated larger average lesion thickness (9.0 vs. 7.3 mm), and had a higher rate of metastasis (50% vs. 33%) compared with BAP1 -retained MBN. BAP1 expression studies may assist in the diagnosis and management of MBN, but further research is needed.